Hubungan Pengetahuan dengan Sikap Ibu Post Sectio Caesarea tentang Mobilisasi Dini - Evi Damayanti; Noor Rochmah Ida Ayu; Tin Utami (Poltekkes Kemenkes Bengkulu, 2021)
Factors that influence mobilization include lifestyle influenced by education and knowledge, disease processes and injury. Post partum mothers with sectio caesarea often complain of pain in the operating area so that mothers are reluctant to do early mobilization. Lack of knowledge about early mobilization in post sectio caesarea mothers can affect the ongoing implementation of mobilization so that it can cause the risk of prolonged bed rest such as blood circulation disorders. The purpose of this study was to determine the relationship between the level of knowledge with the attitudes and behavior of postpartum mothers post sectio caesarea regarding early mobilization. This study used a cross sectional approach involving postpartum mothers post sectio caesarea at the Mother and Child Hospital (RSIA) Bunda Arif Purwokerto. According to the sampling calculation using the Slovin formula, 47 postpartum mothers post sectio caesarea were found to be respondents. The sampling technique used purposive sampling with criteria for postnatal mothers with sectio caesarea more than 4 hours. The instrument used is a questionnaire. Data analyze using spearman rank. The results of this study indicate that there is a relationship between the level of knowledge with the attitude and behavior of postpartum mothers post sectio caesarea regarding early mobilization with p value 0.017 (α <0.05). This study is expected to be an evaluation material to improve the quality of nursing services for post sectio caesarea mothers.